Potassium oxalate-based mouth rinse for rapid relief in dentinal hypersensitivity - Balaji Manohar; Kranthi Kiran Pebbili; Kirti Shukla (Wolters Kluwer Medknow Publications, 2024)
Dentinal hypersensitivity (DHS) affects about 1.3%-92.1% of the population globally and has a significant impact on the quality of life of the affected individuals. Desensitizing agents that directly block the dentinal tubules or cause chemical blocking of the pulpal nerve endings are commonly recommended for the management of DHS. Potassium oxalate (KO) has been used as a desensitizing agent in the management of DHS. This narrative review aimed to assess the literature related to the efficacy of KO as a desensitizing agent, with a focus on mouth rinses containing 1.4% KO. A comprehensive search of the literature was carried out using PubMed and Google Scholar with relevant keywords. The results from the retrieved articles were assessed, and the findings regarding the efficacy of KO in managing DHS were analyzed. Studies suggest that the usage of 1.4% KO mouth rinses results in the occlusion of dentinal tubules by the formation of acid-resistant calcium oxalate crystals within dentinal tubules and on the dentine surface. These calcium oxalate crystals tend to form a strong bond with the inner surface of the dentinal tubules and lower the hydraulic conductivity of the dentine. These actions of KO can ensure both rapid and long-term relief from DHS.